2014
DOI: 10.1111/avj.12197
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of targeted surveillance for screw‐worm fly (Chrysomya bezziana or Cochliomyia hominivorax) in Australia

Abstract: Changes to surveillance at sea ports are proposed to better target areas considered to have a higher relative likelihood of screw-worm fly incursion. These include increasing the trapping intensity along the north and north-east coasts and shifting surveillance activity from the west coast to the south-east.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The floor of the boxes is also spread with material like cornmeal for the purpose of the larvae not being able to [13], then a number of pumpkin fruits are placed in the boxes for the purpose of feeding the adults and in order to be a place for the growth of larvae, after that the boxes are monitored to reach the goal of the third generation of the two species, and after the completion of the growth of the adult larval phase of the third generation in both kinds, the larvae are withdrawn and placed 25 larvae each Kind in 5 transparent plastic boxes with a perforated lid for the purpose of allowing air to breathe the larvae, and each box contains a piece of medical cotton for the purpose of frying the larvae, then each box is sprayed with MgO and TiO2 materials for each kind after mixing them with (1) ml of the insecticide melathion and one liter of Distilled water for both substances separately and then the combat larvae are observed in the cans and for each nanomaterial to record the results and statistically analyze them.…”
Section: Methodsmentioning
confidence: 99%
“…The floor of the boxes is also spread with material like cornmeal for the purpose of the larvae not being able to [13], then a number of pumpkin fruits are placed in the boxes for the purpose of feeding the adults and in order to be a place for the growth of larvae, after that the boxes are monitored to reach the goal of the third generation of the two species, and after the completion of the growth of the adult larval phase of the third generation in both kinds, the larvae are withdrawn and placed 25 larvae each Kind in 5 transparent plastic boxes with a perforated lid for the purpose of allowing air to breathe the larvae, and each box contains a piece of medical cotton for the purpose of frying the larvae, then each box is sprayed with MgO and TiO2 materials for each kind after mixing them with (1) ml of the insecticide melathion and one liter of Distilled water for both substances separately and then the combat larvae are observed in the cans and for each nanomaterial to record the results and statistically analyze them.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies emphasized that temperature is the most significant variable that affects OWSF distribution 14,15 . Our model agrees with this finding, and the ambient temperature variables were the most effective bioclimatic variables of jackknife test that affected OWSF distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In the real world, Australia has already faced some cases of OWSF detection on quarantines on northern harbors due to livestock trades including a collection of adult male and female flies 52 . So, the resultant models act as a warning guard for Australian quarantine authority to avoid the possible invasion of OWSF to their northern territory 14 . A www.nature.com/scientificreports www.nature.com/scientificreports/ similar status of incursion has occurred in Libya with NWSF 20,53 , the FAO estimated the cost of eradication-via a sterile insect technique-to reach US$750 million 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers at the Department of Agriculture used factors affecting the ability of the screw-worm fly to establish and reproduce to build a map of Australia identifying those areas with the highest likelihood of screw-worm fly incursion. 6 Australia remains the only continent with a suitable climate that is free of screw-worm fly and an incursion would have a tremendous impact on grazing industries, with huge losses in production and costs associated with control measures. The study results indicated that, under average environmental conditions, an incursion of screw-worm fly in Australia is relatively more likely to occur along the north coast, down the eastern seaboard or in the south-east.…”
Section: Production Animalsmentioning
confidence: 99%